Recognizing a “Different Drum” Through Close-Reading Strategies - Cindy Lassonde (Networks: An Online Journal for Teacher Research, 2009)
Every day 7,000 high-school students drop out of school (Alliance for Excellent Education, 2005). Students reading at basic levels are more prone to drop out than those reading at higher levels. According to the latest results on the National Assessment of Educational Progress 2005 Mathematics and Reading Trial Urban District Assessment, commonly called the “Nation’s Report Card,” the percentage of students reading below the basic level is high. Based on my concern over this critical issue of students’ reading comprehension abilities, I decided to explore the development of comprehension skills through close-reading strategies by spending time in a high-school classroom in a small, rural school district in upstate New York. As a college professor from a nearby teacher-education institution, I contacted and worked with an eleventh-grade English teacher to develop a unit on individualism with the goal of fostering the growth and development of the students’ abilities to generate a meaningful and insightful dialogue with the writer through close-reading strategies.